2023
DOI: 10.1161/circresaha.122.321398
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Human Cardiac Cell Development due to NOTCH1 Deficiency

Abstract: BACKGROUND: NOTCH1 pathogenic variants are implicated in multiple types of congenital heart defects including hypoplastic left heart syndrome, where the left ventricle is underdeveloped. It is unknown how NOTCH1 regulates human cardiac cell lineage determination and cardiomyocyte proliferation. In addition, mechanisms by which NOTCH1 pathogenic variants lead to ventricular hypoplasia in hypoplastic left heart syndr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 84 publications
1
14
0
Order By: Relevance
“…Overall, the findings of Ye et al 9 highlight the power of hiPSCs, genome editing, and single-cell RNA sequencing as a unique toolkit to gain new insights into the comprehension of the mechanisms that underlie congenital heart defects etiology. With this human model in hand, they showed that NOTCH1 genetic ablation impact early stages of human cardiogenesis by blocking ventricular-like cardiomyocyte differentiation and proliferation and inhibiting cardiac mesoderm cell differentiation into first heart field progenitors that represent the major source of left ventricle Recently, 3D self-organizing cardiac organoids have been generated.…”
Section: Editorialmentioning
confidence: 98%
See 3 more Smart Citations
“…Overall, the findings of Ye et al 9 highlight the power of hiPSCs, genome editing, and single-cell RNA sequencing as a unique toolkit to gain new insights into the comprehension of the mechanisms that underlie congenital heart defects etiology. With this human model in hand, they showed that NOTCH1 genetic ablation impact early stages of human cardiogenesis by blocking ventricular-like cardiomyocyte differentiation and proliferation and inhibiting cardiac mesoderm cell differentiation into first heart field progenitors that represent the major source of left ventricle Recently, 3D self-organizing cardiac organoids have been generated.…”
Section: Editorialmentioning
confidence: 98%
“…One of the main advantages of cardiac stepwise-directed differentiation of hPSCs as a human cardiogenesis platform is the unique possibility to profile the genetic networks and mutation-associated perturbations from pluripotency through stage-specific transitions in cardiac differentiation. Here, Ye et al 9 employed single-cell RNA sequencing to interrogate for the first time the impact of NOTCH1 KO at different stages of cardiac lineage specification. While there were no major changes before day 5 of differentiation (cardiac mesoderm), the amount of second heart field progenitors and epicardial cells was increased in NOTCH1 KO cells.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…2 Human iPSC-derived cardiomyocytes (iPSC-CMs) were generated by sequential modulation of Wnt signaling. 3 Immunofluorescence staining indicated the intercalated…”
mentioning
confidence: 99%